Data analysis and discussion of thermal response test under a power outage and variable heating power. (August 2020) - Song, Wei; Zheng, Tuanfeng; Liu, Xiaoxiu; Yang, Jiaming; Zhang, Changxing
Abstract: In this research, a comprehensive study of power outage and variable heating power were conducted during an in-situ thermal response test (TRT) with a 261-m deep double U-tube borehole heat exchanger. The TRT data obtained during a power outage were measured using the indirect, superposition, equivalent time, and separation methods to obtain the thermal properties of rock-soil. The thermal conductivity of rock-soil, volumetric heat capacity, and thermal resistance were 1.21 W/(m·°C), 2413 kJ/(m 3 ·°C), and 0.41 m 2 ·°C/W, respectively. In the analysis of the test data of the variable heating power conditions, the additional heating as a result of the pump power cannot be ignored, and heat generated by the circulating water pump was stable. The heat transfer rate and average fluid temperature gradually stabilized as the test progressed, and the relationship between them is linear. The trends in the heat exchange rate and average fluid temperature after changing the heating power were expressed using a formula. A thermal response test method with variable heating power was proposed for this test, and the thermal conductivity and initial ground temperature of rock-soil were obtained using this method.